Mathematics at work – researching adults’ mathematics-containing competences - Wedege, Tine (NOMAD Nordic Studies in Mathematics Education, 2004)
In the workplace, mathematics is integrated in three dimensions of technology − in technique and machinery, in work organisation and in human competences and qualifications. In the article, methodology in researching mathematics-containing competences is the focus. It is argued that the complexity in adults’ mathematics at work has to be investigated in a borderland between mathematics education and adult education research, where the import and reconstruction of theories and concepts are important tasks. An operational methodology, based on a model for analysing numeracy, is presented. This methodology – by virtue of the conceptual development associated with it − has also been useful in teacher training.